THE ROLE OF CHRISTIAN RELIGIOUS EDUCATION TEACHERS IN THE CHARACTER FORMATION OF ELEVENTH-GRADE STUDENTS AT SMA NEGERI 1 SIBOLGA, ACADEMIC YEAR 2024/2025 - Saragih, Novita Romauli; Karo-Karo, Selamat; Lumban Gaol, Bulan Puspita Sari; Wiharjokusumo, Padriadi; Girsang, Dameria (Jurnal Ilmiah Akomodasi Agung, 2025)
Character education is a central mandate in Indonesia’s national education framework, emphasizing the development of moral integrity, responsibility, and spiritual maturity. Christian Religious Education (CRE) teachers play a strategic role in shaping students’ character by integrating biblical values with moral instruction, role modeling, and spiritual mentoring. This study examines how CRE teachers contribute to character formation among eleventh-grade students at SMA Negeri 1 Sibolga during the 2024/2025 academic year. Using a qualitative descriptive approach, this research collected data through interviews, observations, and document analysis. The findings indicate that CRE teachers perform four crucial functions: (1) moral educator, (2) role model, (3) motivator, and (4) spiritual mentor. These roles collectively enhance students’ honesty, discipline, responsibility, tolerance, respectfulness, and spiritual devotion. However, teachers face significant challenges, including digital media influence, peer pressure, and inconsistent parental involvement. The study concludes that CRE teachers significantly influence character formation when supported by consistent modeling and collaborative school–family partnerships